DESCRIPTIVE ANALYSIS OF FACTORS THAT INFLUENCE LOCATION DETERMINATION OF PT YAKULT FACTORY SEREMBAN MALAYSIA - Dima Rianda; Kuncorisidi Kuncorisidi; Mutqi Sopiawadi (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
Determining the location of the business is an activity that is not easy, many factors affect the decision in determining the location because it involves the company's operational costs. This study aims to determine the factors that were taken into consideration by PT Yakult Factory Seremban Malaysia in choosing the current location of the factory. This study uses descriptive qualitative methods, data collected through interviews and observations in the field as well as reviewing secondary data related to in-depth research object information from informants who have been determined and carried out continuously until saturated. The results of the study revealed that the factors that were taken into consideration in selecting the business location of PT. Yakult Factory Seremban Malaysia namely; 1) availability of labor, 2) availability of electricity, 3) transportation facilities, 4) health, safety and fire prevention services, 5) local government regulations, 6) community attitudes, 7) land and building costs, 8) Possible expansion 9) Road Width. 10) Sewer 11) Location of raw materials 12) Market location. Factors that are not given much attention in determining the business location for PT. Yakult Factory Seremban Malaysia namely; 1) housing, education, shopping, and telecommunications facilities; 2) Parking area